2012 IEEE Global Humanitarian Technology Conference 2012
DOI: 10.1109/ghtc.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Improving Maternal Labor Monitoring in Kenya Using Digital Pen Technology: A User Evaluation

Abstract: Paper-based systems for monitoring maternal labor have been shown to reduce life-threatening complications in low-resource environments; however, significant barriers exist to the use of these tools in developing countries. This paper presents the PartoPen -a digital pen system that enhances a common labormonitoring form known as the partograph. The PartoPen system provides real-time data feedback and reinforces birth attendant training, while retaining the paper-andpen interface currently used by most healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The results of this study showed that the use of the partograf-based computer system allows midwives to perform the process, partograf-based computer system will minimize the error rate and has a good level of truth, This is in line with research conducted by [5,6], who get that the use of electronic partograf more effectively and efficiently with limited human resources so that the impact on the completeness of on charging partograf, and reduce the error rate and the use of hardware and software as a tool to monitor progress of labor can be used as a tool to train health workers on how to use partograf.…”
Section: Discussionsupporting
confidence: 86%
“…The results of this study showed that the use of the partograf-based computer system allows midwives to perform the process, partograf-based computer system will minimize the error rate and has a good level of truth, This is in line with research conducted by [5,6], who get that the use of electronic partograf more effectively and efficiently with limited human resources so that the impact on the completeness of on charging partograf, and reduce the error rate and the use of hardware and software as a tool to monitor progress of labor can be used as a tool to train health workers on how to use partograf.…”
Section: Discussionsupporting
confidence: 86%
“…Three tools had undergone formative assessment in form of user or cost evaluations [23,26,27]. We retrieved literature on a tool that was designed and tested in 2007, but we did not get publications on its advancement.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can help the health workers in knowing the speed of the postpartum hemmorhage estimation at the stage III and IV, so that early detection of postpartum emergency such as loss of more than 500 cc of blood after child birth (Hancock, Andrew, & Dame, 2015;Underwood, Sterling, & Bennett, 2012). This digital scale can help people to avoid postpartum hemorrhage, to improve the diagnosis and the management strategies.…”
Section: Discussionmentioning
confidence: 99%